Ornithine transcarbamylase deficiency and pregnancy: A case series and review of recommendations - Gabriella Pinho; Gabriela Ross; Kaila Krishnamoorthy; Christina Kresge; Ling Yu Shih; Joseph J. Apuzzio; Shauna F. Williams (Elsevier, 2022)
Background: Ornithine transcarbamylase deficiency (OTCD) is a rare disorder of the urea cycle that obstetricians should be aware of in order to guide management for pregnant carriers of the X-linked gene that causes the condition. Cases: We present the pregnancy management and outcomes of two women with OTCD. The particular manifestations of the disease drive antenatal, intrapartum and postpartum management. Conclusion: Preconception counseling, early prenatal diagnostics and multidisciplinary intrapartum and postpartum management plans contribute to improved outcomes for patients.